The clinical efficacy of proprioceptive neuromuscular facilitation technique in the treatment of scapulohumeral periarthritis: a systematic review and meta-analysis - Chengyu Zhu; Xueyan Huang; Jiaying Yu; Ying Feng; Haifang Zhou (BMC Musculoskeletal Disorders)
Abstract Background Scapulohumeral periarthritis (SP) is a disease caused by chronic inflammation of the shoulder soft tissue area, which is characterized by shoulder pain and limited mobility. Due to the long course of disease, it often has a great impact on the life and work of patients. Objectives The purpose of this study was to systematically evaluate the effect of proprioceptive neuromuscular facilitation (PNF) stretching technique in the treatment of SP. Methods A systematic search of 10 databases such as China National Knowledge Infrastructure (CNKI), China Biomedical Literature Database, Weipu, Wanfang, PubMed, Embase, Web of Science, Cochrane Library, Clinical Trials, and China Clinical Trial Registry Platform was performed. The retrieval time was from inception to January 2024. Two researchers screened the literature according to the inclusion and exclusion criteria, extracted the data, and evaluated the quality.Revman5.3 software was used for meta-analysis, and only descriptive analysis was performed on the outcome indicators of the number of literature ≤ 2. Results A total of 12 articles were included, including 968 patients. The results of Meta-analysis showed that PNF technique could reduce pain intensity ((Visual analog scale (VAS) score (SMD = -0.67, 95% CI [-1.18, -0.15], P = 0.03), Japanese Orthopaedic Association (JOA) score (subjective pain score standard) (SMD = 0.79, 95% CI [0.23,1.35], P < 0.01)), improve the shoulder function of patients (SMD = 1.13, 95% CI [0.96,1.31], P < 0.01), and improve the patient’s daily living ability (SMD = 1.06, 95% CI [0.77,1.34], P < 0.01). The results of descriptive analysis showed that the PNF technique could improve the psychological state of patients with scapulohumeral periarthritis to a certain extent. Conclusion The PNF technique can help patients with scapulohumeral periarthritis to relieve pain, improve shoulder function, and strengthen daily living ability. In addition, a good psychological state is conducive to better recovery of patients ' health. In clinical work, medical staff should pay attention to the psychological state of patients with SP. Clinical trial number Not applicable.